Implementasi Kebijakan Kartu Identitas Anak (KIA) oleh Dinas Kependudukan dan Pencatatan Sipil Kabupaten Karimun - Imel Kessumawati; Arif Rahman Hakim (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
The Child Identity Card (KIA) policy is one of the policies that has been issued by the government in accordance with Minister of Home Affairs Regulation Number 2 of 2016. The policy regarding child identity cards (KIA) started in 2016 in each Regency/City, while the implementation of this policy is implemented in Karimun Regency itself started in May 2018. In its implementation there were several problems that emerged where there were still many children under the age of 17 who still did not have a child identity card (KIA), of course this was not in line with the number of children in Karimun Regency which each year is increasing. The aim of this research is to determine the implementation of the child identity card (KIA) policy and to find out what are the inhibiting factors. The research method used in this research is a qualitative descriptive method. The data collection techniques used were observation, interviews and documentation. This research uses the main theory of Edward III, seen from 4 variable indicators that can influence the implementation of a policy. The results of the research show that the implementation of the child identity card (KIA) policy by the Population and Civil Registration Service of Karimun Regency, when viewed from the communication aspect, has run optimally. Judging from the aspect of resources, it is quite competent, and in terms of quality it is adequate. Judging from the disposition aspect, the officers/employees uphold high enthusiasm in implementing policies and carrying out their assigned tasks. Then, if we look at the bureaucratic structure aspect, officers/employees can always manage well in collaborating with each other. The inhibiting factor in this research is that the availability of budget to finance blanks is still relatively lacking, many applicants for child identity cards (KIA) have not yet completed the requirements, so this makes it difficult for officers/employees to process them.